Graphene synthesis, characterization and its applications in nanophotonics, nanoelectronics, and nanosensing - Akbar, F.; Kolahdouz, M.; Larimian, Sh; Radfar, B.; Radamson, H. H. (Journal of materials science. Materials in electronics, 2015)
In the last decade, as semiconductor industry was approaching the end of the exponential Moore’s roadmap for device downscaling, the necessity of finding new candidate materials has forced many research groups to explore many different types of non-conventional materials. Among them, graphene, CNTs and organic conductors are the most successful alternatives. Finding a material with metallic properties combined with field effect characteristics on nanoscale level has been always a dream to continue the ever-shrinking road of the nanoelectronics. Due to its fantastic features such as high mobility, optical transparency, room temperature quantum Hall effect, mechanical stiffness, etc. the atomically thin carbon layer, graphene, has attracted the industry’s attention not only in the micro-, nano-, and opto-electronics but also in biotechnology. This paper reviews the basics and previous works on graphene technology and its developments. Compatibility of this material with Si processing technology is its crucial characteristic for mass production. This study also reviews the physical and electrical properties of graphene as a building block for other carbon allotropes. Different growth methods and a wide range of graphene’s applications will be discussed and compared. A brief comparison on the performance result of different types of devices has also been presented. Until now, the main focus of research has been on the background physics and its application in electronic devices. But, according to the recent works on its applications in photonics and optoelectronics, where it benefits from the combination of its unique optical and electronic properties, even without a bandgap, this material enables ultrawide-band tunability. Here in this article we review different applications and graphene’s advantages and drawbacks will be mentioned to conclude at the end.